Medial meniscus transplantation using cyanoacrylate in rabbits - Reckers,Leandro José (2006)
PURPOSE: To evaluate meniscal transplantation using as fixation method a synthetic glue derived from cyanoacrylate acid. METHODS: Twenty rabbits were used, of which 10 for autologous transplantation and 10 for homologous transplantation. For the autologous transplantation the meniscus was removed, and then transplanted in the same animal, using the synthetic glue. For the homologous transplantation, the study was divided into two stages: 1- Removal of the meniscus which was maintained at a temperature of 73ºC. 2- Use of cyanoacrylate acid-derived surgical adhesive for meniscal retransplantation in a different rabbit 30 days after the transplant. RESULTS: Due to complications, euthanasia had to be anticipated to the 15th day in the homologous group and to the 18th day in the autologous group. Macroscopically, knees submitted to transplantation presented whitish secretions from the surgical incision up to deep planes. Necrosis was observed in both groups. Statistical analysis has shown that mild (p=0.043) and moderate (p=0.001) complications emerged in a significantly earlier way in the homologous group, where euthanasia was also performed earlier (p=0,005). CONCLUSION: Synthetic surgical adhesives derived from cyanoacrylate acid promoted cortical to medullary bone necrosis bone in both groups.